Persian Version of Quality Patient Care Scale: A Letter to the Editor - Amir Hossein Gholami; Amir Sadeghi; Arash Khalili; Hojatolah Gharaee (نشریه پرستاری ایران, 2023)
Nursing is an independent discipline and a branch of medical sciences. Its mission is to provide the necessary health, treatment and rehabilitation services at the highest level to ensure, maintain or improve the health of society. Davis et al. (2005) emphasized the importance of measuring patient care quality. In their study, a standard questionnaire named quality patient care scale (QUALPAC) was used to measure the quality of patient care. This tool has been used since 1975 in different countries. Different studies have used this questionnaire with 68 items. The Persian version of this tool was validated in Iran by Khoshkho et al. Based on their results, the Persian version has 72 items rated on a five-option Likert scale. Different versions of QUALPAC been used in various studies conducted in Iran, and its reason is not clear. For example, in the study by Heydari and et al., the 65-item version of QUALPAC was used, with no reference was provided for the applied version.